RAPID LAND TENURE ASSESSMENT OF BAGHDAD CITY IN IRAQ 2010 - العمار, د.علي كريم; خضير, د .عامر شاكر; الهماوندي, د.رافد عبداللطيف الهماوندي عبداللطيف (Journal of Planner and Development, 2012)
The purpose of this study is to describe the extent and nature of informal tenure practices in urban areas in Iraq, through undertaking a rapid assessment in Baghdad city. The UN-HABITAT 2008 publication Secure Land Rights for All discusses the importance of access and rights to land throughout the developing world. Secure land rights are critical to development and poverty reduction, and the greatest challenge in providing secure land rights are in urban areas, where overcrowding can lead to a number of informal tenure practices ranging from individually unregistered or unauthorised housing, to large informal settlements. Access to land is a fundamental basis for human shelter, food production, and other economic activity. Secure rights to land encourage people to invest in improved dwellings, and the land itself. Secure land rights also enable people to access public services and sources of credit. Yet, land everywhere is under pressure from population growth and economic development. Land that is in demand for residential use also attracts increasing commercial interest, and the higher returns commercial builders and sometimes taxes can generate for governments can crowd out those looking for homes. In addition to this, unprecedented numbers of people are moving to urban areas, but at the same time few of these urban areas – particularly in the developing world – have been planned to absorb these influxes of people. The result is a growing urbanization of poverty, a growth of slums, and a rapid rise in the number of people worldwide without   land tenure, tenure security, or property rights